2013
DOI: 10.1159/000355748
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Dysfunction in Sickle Cell Disease

Abstract: Background/Aims: Kidney abnormalities are one of the main chronic complications of sickle cell disease (SCD). The aim of this study is to investigate the occurrence of renal tubular abnormalities among patients with SCD. Methods: This is a prospective study with 26 SCD adult patients in Brazil. Urinary acidification and concentration tests were performed using calcium chloride (CaCl2), after a 12h period of water and food deprivation. Fractional excretion of sodium (FENa), transtubular po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The serum level of sodium was significantly lower in the SCD patients, compared with the controls. This is in line with other studies 7-11 conducted elsewhere, which reported low serum levels of sodium in the sickle cell patients, compared with their ‘healthy’ counterparts. The reduced serum level of sodium in the SCD patients may be due to at least, in part, a possible loss of some body fluids and electrolytes, as well as inflammation and the underlying chronic condition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The serum level of sodium was significantly lower in the SCD patients, compared with the controls. This is in line with other studies 7-11 conducted elsewhere, which reported low serum levels of sodium in the sickle cell patients, compared with their ‘healthy’ counterparts. The reduced serum level of sodium in the SCD patients may be due to at least, in part, a possible loss of some body fluids and electrolytes, as well as inflammation and the underlying chronic condition.…”
Section: Discussionsupporting
confidence: 93%
“…The result from this current study highlights the potential use of electrolyte levels as biomarkers of SCD. Imbalance homeostasis of electrolytes including sodium, potassium, and chloride has been described in relation with sickling and increased dehydration in sickle cell patients outside Ghana, 7,8,11 with very few studies in Africa. 9,10 The sodium-potassium ATPase activity has been shown to be more active in sickle cell and contributes to cell dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism of increased GFR and renal plasma flow in patients with SCD is related to compensatory hypersecretion of vasodilator prostaglandins in response to sickling (5,11,12). During adolescence both GFR and RPF are normal, but are frequently subnormal after the age of 40.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of metabolic acidosis in patients with moderate SCD genotype is less clear. Etiologies for metabolic acidosis in SCD may include impaired ammonium availability, hyporeninemic hypoaldesteronism, or impaired distal tubular acidification capacity (5,6,25,27). Consistent with the literature, we observed a higher prevalence of metabolic acidosis in patients with severe SCD genotype (21%) and a higher prevalence of metabolic acidosis in patients with moderate SCD genotypes (11%) compared with African Americans from the NHANES (5%).…”
Section: Discussionmentioning
confidence: 99%